RESPON EMPAT KELAPA HIBRIDA HARAPAN TERHADAP PENYAKIT BUSUK PUCUK DAN GUGUR BUAH - A. A. LOLONG; E. T. TENDA; J. C. ALOUW (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
Response of four new coconut hybrids to bud rot and premature nutfull diseasesThe objective of Ihe experiment was to find out Ihe resistance of four new coconut hybrids GRA x DMT. GKB x DMT, GKN x DTE. GKB x DTE against bud rol and premature nutfall diseases due lo Phytophthora palmivora. The field observation on bud rot was conducted in coconut trial plots at Kima Atas experimental garden. Minahasa District, North Sulawesi Province for 4 years (1995-1998). The field trial was arranged in a randomized block design with 6 treatments (4 coconut hybrids. 2 control) and 60 replicates The experiment under laboratory condilion was conducted to know the artificial infection development of P palmivora on coconut nut The experiment was arranged in a completely randomized design with 6 treatments (4 coconut hybrids, 2 control) and 10 replicates. The result of the field observation showed that percentage of coconut infection by bud rot per cultivar were PB-121 (23.33%) as the highest and then followed by GKN x DTE (8.33%), KHINA-1 (5.0%) and GKB x DMT (3.33%) while cultivars of GKB x DTE and GRA x DMT unlil 4 years observation were not infected by bud rot In laboratory trial, Ihe growth rate of pathogen was very high on KHINA-1 (12.62 mm2/day). The growth rate of pathogen in GKB x DIE and GRA x DMT were slowest (8 9 mm'/day) while those in PB- 121, GKN x Dll and GKB x DMT were moderate (9-10.2 mm2/day).